HUBUNGAN TINGKAT PENGETAHUAN PERAWAT DENGAN PENERAPAN UNIVERSAL PRECAUTION PADA PERAWAT DI BANGSAL RAWAT INAP RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA - Yulianti, .; Rosyidah, .; Hariyono, Widodo (Universitas Ahmad Dahlan, 2011)
Background: Universal Precaution is common caution which is nursing must be obeyed by nurse or medical labor in doing every nursing action towards the patient to protect from some of infection material. The nurse's knowledge about the universal precaution is needed to be high on guard towards spreading disease. This research purposes to know the relation between nurse's knowledge in application universal precaution in PKU Muhammadiyah Yogyakarta hospital. Method: This was an observational analytic with research using cross sectional approach. The population in this research is the nurse in patient II and III classes amounted to 34 nurses. The sample taken by total sampling technique is number of 34 nurses. The data of research is taken by observation and spreading question and processed by using the chi square test. Result: The degree of nurse's knowledge in hospital categorize high amounted to be 26 nurses by percentage of 76,47 %. (1) the degree of nurse's knowledge in application wash hand to the nurse categorize good amounted by percentage of 79,41%, gotten the score p= 0,019, it means that there is a significant relation between the degree of nurse's knowledge with the application of wash hand to the nurse in hospitalized ward of PKU Muhammadiyah Yogyakarta hospital (2) the degree of nurse's knowledge with application of antiseptic use and the disinfectant to the nurse categorize good amounted by percentage of 82,35%, gotten the score p= 0,006, it means that there is a significant relation between the degree of nurse's knowledge with the application of antiseptic use and the disinfectant to the nurse in PKU Muhammadiyah Yogyakarta hospital. (3) The degree of nurse's knowledge with the application the use of self protector to the nurse categorize good amounted by percentage of 85,29%, gotten the score p= 0,037, means that there is a significant relation between the degree of nurse's knowledge with application of self protector use to the nurse in the PKU Muhammadiyah Yogyakarta hospital. (4) the degree of nurse's knowledge with the application the discharge of medical rubbish to the nurse categorize good amounted by percentage of 85,29%, gotten the score p= 0,001, means there is a significant relation between the degree of nurse's knowledge with the application of medical rubbish discharge to the nurse in PKU Muhammadiyah Yogyakarta hospital. Conclusion: There was a significant relationship between the degree of nurse's knowledge with application universal precaution to the nurse in patient in PKU Muhammadiyah Yogyakarta hospital. Key word: the nurse, the degree of knowledge, nosocomial infection, universal precaution